Co-Expression Networks Reveal Potential Regulatory Roles of miRNAs in Fatty Acid Composition of Nelore Cattle - de Oliveira, Priscila S.N.; Coutinho, Luiz L.; Cesar, Aline S.M.; Diniz, Wellison J. da Silva; de Souza, Marcela M.; Andrade, Bruno G.; Koltes, James E.; Mourão, Gerson B.; Zerlotini, Adhemar; Reecy, James M.; Regitano, Luciana C.A. (Frontiers in Genetics, 2019)
Fatty acid (FA) content affects the sensorial and nutritional value of meat and play a significant role in biological processes such as adipogenesis and immune response. Well known, in beef the main FAs associated with these biological processes are oleic acid (C18:1 cis9, OA) and conjugated linoleic acid (CLA-c9t11), which may have beneficial effects on metabolic diseases such as diabetes type 2 and obesity. Here, we performed differential expression and co-expression analyses; Weighted Gene Co-expression Network Analysis (WGCNA) and Partial Correlation with Information Theory (PCIT); to uncover the complex interactions between miRNAs and mRNAs expressed in skeletal muscle associated with FA content. miRNA and mRNA expression data were obtained from skeletal muscle of Nelore cattle that had extreme genomic breeding values for OA and CLA. Insulin and MAPK signaling pathways were identified by WGCNA as central pathways associated with both of these fatty acids. Co-expression network analysis identified bta-miR-33a/b, bta-miR-100, bta-miR-204, bta-miR-365-5p, bta-miR-66, bta-miR-411a, bta-miR-136, bta-miR-30-5p, bta-miR-146b, bta-let-7a-5p, bta-let-7f , bta-let-7, bta-miR 339, bta-miR-10b, bta-miR 486, and the genes ACTA1 and ALDOA as potential regulators of fatty acid synthesis. This study provides evidence and insights into the molecular mechanisms and potential target genes involved in fatty acids content differences in Nelore beef cattle, revealing new candidate pathways of phenotype modulation that could positively benefit beef production and human consumption.